Game Edukasi Metamorfosis Hewan Dengan Augmented Reality Berbasis Android - Bonanza, Muhammad Jodie; Fathurriza, Ari; Sudiatmika, I Putu Gede Abdi; Rahardian, Rifky Lana (Universitas Tabanan, 2022)
There are several problems found in elementary school learning. One of them is learning media. Currently, there are many types of learning media, some are digital-based such as learning media using audio media, multimedia computers, and there are also conventional learning that still uses books, pictures in the teaching and learning process such as metamorphosis learning which still uses books in the teaching process. To improve the learning process at SD No. 3 Ungasan in grades 3,4, and 5 in the field of natural science, an educational game of animal metamorphosis was made with android-based augmented reality as a learning medium. The purpose of this research is to build an Android-based augmented reality animal metamorphosis educational game to help elementary school students and teachers. This educational game is built in the C# programming language using the Unity Engine. The method used in making this game is Multimedia Development Life Cycle (MDLC). The test system used is blackbox testing, where the results of system testing conclude that the system is in line with expectations. Based on the results of user testing, this educational game got a 100% increase in satisfaction from 17 responses consisting of 2 teachers and 15 students.